Cesarean section classification according to Robson's system in a private IPS in Cali, 2017 - Mosquera Agudelo, José Luis (2022)
Objective: To characterize cesarean sections according to the Robson classification system in a private high complexity PIS, in the period between January 1 - December 31, 2017. Methods: Descriptive, retrospective, cross-sectional study conducted in a private SPI in the city of Cali. The study included pregnant women admitted for delivery care in 2017, a database was constructed in Microsoft Excel 2010, with the variables defined in Robson's classification. The rate of cesarean sections, the relative size of each group and the relative contribution of each group to the overall rate of cesarean sections were calculated, as well as the causes of cesarean sections were analyzed. The results are presented in tables. Results: The overall cesarean section rate was 35.4 %. The groups with the highest contribution to the total percentage of cesarean sections were groups 2, 1 and 10 with 20.4 %, 3.9 % and 3.3 %, respectively. History of previous cesarean section was the main cause. Conclusions: Using Robson's classification, it can be concluded that it is possible to reduce the rate of cesarean section rate by 14 % by intervening in the history of previous cesarean section.